Simultaneous progression patterns of scoliosis, pelvic obliquity, and hip subluxation/dislocation in non-ambulatory neuromuscular patients: An approach to deformity documentation. (October 2015) - Patel, Janki; Shapiro, Frederic
Background: A triad of deformities—thoracolumbar scoliosis, pelvic obliquity, and femoral head (hip) subluxation/dislocation—occurs frequently in non-ambulatory neuromuscular patients, but their close inter-relationship is infrequently appreciated or quantified. We propose a deformity documentation approach to assess each component simultaneously. Methods: The documentation assesses each component for maximal functional level, deformity, and flexibility/rigidity: deformity from antero-posterior radiographs (scoliosis—maximal functional position, pelvic obliquity—sitting, hip position—supine) and flexibility/rigidity from extent of repositioning on supine (spine, pelvis) and frog lateral (hip) radiographs. The approach was applied in 211 patients: Duchenne muscular dystrophy (110), spinal muscular atrophy (49), cerebral palsy (26), and other neuromuscular disorders (26). Results: Measurement of 2124 radiological data points allowed for deformity (mild to moderate to severe) and flexibility/rigidity (fully reducible to partially to non-reducible) gradations for scoliosis, pelvic obliquity, and hip subluxation/dislocation. The charting documented: (1) numerical deformity and flexibility/rigidity changes [ x -axis: age; y -axis: angulation (scoliosis and pelvic obliquity) and percent coverage (hip subluxation or dislocation) from 0–120]; and (2) grade deformity and flexibility/rigidity changes [ x -axis: age; y -axis: deformity and flexibility/rigidity, following conversion of numerical measurements to a 1–5 grade scale]. In subgroups with the most extensive documentation, thoracolumbar and lumbar scoliosis extended into the sacrum with 98 % (114/116) accompanied by pelvic obliquity; and scoliosis developed more rapidly than hip deformity in 44 % (28/63), scoliosis and hip deformity developed at the same time in 40 % (25/63), and hip deformity developed more rapidly than scoliosis in 16 % (10/63) (Pearson's chi-squared test p = 0.0501, almost significant). Conclusion and significance: Documentation of the triad of neuromuscular deformities is applicable to all diagnoses; it outlines maximal functional level, deformity, and flexibility/rigidity at each site; and it shows the relationship between spine, pelvic, and hip deformation. Prospective charting will enhance both clinical management and clinical research into neuromuscular deformity.